Scientific and targeted prevention and control measures to optimize COVID‐19 response - Released by the Taskforce for Joint Prevention and Control Mechanism for COVID‐19 under the State Council and the National Health Commission of P.R. China on November 11, 2022 (Wiley, 2023)
Abstract Since the outbreak of the COVID‐19 pandemic, under the strong leadership of the Central Committee of the Communist Party of China and President Xi Jinping, China has made firm decisions to prioritize people's lives and health. Efforts have been made to avoid foreign imported infection and domestic rebound of COVID‐19 cases; the "dynamic zero COVID" policy has been executed without wavering; and the prevention and control measures have been optimized and improved in response to changing circumstances, actively responding to the impact caused by multiple waves of COVID‐19 surge globally. China has made extraordinary efforts to safeguard people's lives and health. Meanwhile, prevention and control measures were timely updated to coordinate with economic and social development. On November 10, the Standing Committee of the Central Political Bureau held a meeting to discuss the latest situation of the COVID‐19 pandemic in China. Twenty measures (referred to as "the 20‐point measures") were officially announced to further optimize the COVID‐19 response. The latest prevention and control measures involve the requirements and guidance for isolation at home, high‐risk area delineation, nucleic acid testing, international inbound flights and travelers, vaccination rollout, medical resource preparedness, and protection for special places and vulnerable population.